The Influence of the Implementation of Simple Accounting and Financial Literacy on Increasing the Income of MSMEs in East Medan - Berupilihen Br Ginting; Tyus Windi Ayuni; Adi Harianto; Amin Hou; Rafida Khairani (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
This study seeks to analyze the influence of simple accounting practices and financial literacy on the income growth performance of micro, small, and medium enterprises (MSMEs) in Medan Timur. Simple accounting is operationalized through key indicators, including systematic record-keeping, preparation of financial reports, and consistency in bookkeeping practices. Financial literacy is assessed based on the level of understanding of fundamental financial concepts, financial planning capabilities, and the ability to make informed financial decisions in business contexts. Meanwhile, income growth performance is measured using indicators such as increased sales, profit growth, and overall financial stability. The study adopts a quantitative research design, employing a survey method as the primary data collection technique. A total of 75 MSME actors in Medan Timur were selected as respondents using purposive sampling. Data were gathered through structured questionnaires specifically developed to measure the research variables. The collected data were subsequently analyzed using multiple linear regression to evaluate the magnitude and significance of the relationships between variables. The findings reveal that both the implementation of simple accounting and financial literacy exert a positive and statistically significant effect on MSME income growth. Accurate and consistent financial recording enables business owners to better monitor and control their financial performance, while a higher level of financial literacy enhances their capacity to make strategic and effective financial decisions. These results underscore the importance of strengthening basic accounting practices and improving financial knowledge as key drivers for sustainable income growth and long-term business development among MSMEs in Medan Timur.